2010 35th IEEE Photovoltaic Specialists Conference 2010
DOI: 10.1109/pvsc.2010.5614244
|View full text |Cite
|
Sign up to set email alerts
|

Copper as conducting layer in advanced front side metallization processes for crystalline silicon solar cells, exceeding 20% on printed seed layers

Abstract: Our work deals with the creation of copper-containing stack systems for the front side metallization of silicon solar cells. In this contribution, we give an overview of different approaches from our labs. We have developed processes to apply nickel diffusion barriers onto seed layers and directly onto silicon with both electrolytic and electroless processes. These are reinforced by a light-induced copper plating process. On aerosol-printed seed layers, cell efficiencies equal to those of reference cells with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Moreover, the proposed replacement of expensive silver front contacts with low-cost copper-plated contacts might further increase the probability of copper contamination in the solar cell line. 5 Therefore, copper might well be the culprit behind LID in some solar cell studies. 6 Recently, much effort has been put into mitigating lightinduced degradation.…”
mentioning
confidence: 99%
“…Moreover, the proposed replacement of expensive silver front contacts with low-cost copper-plated contacts might further increase the probability of copper contamination in the solar cell line. 5 Therefore, copper might well be the culprit behind LID in some solar cell studies. 6 Recently, much effort has been put into mitigating lightinduced degradation.…”
mentioning
confidence: 99%
“…Ni/Cu has shown some good results for solar cell performance in terms of improved FFs and higher efficiencies. The overall cost per watt-peak (W p ) can also be decreased as the copper is cheaper than Ag (about 100 times) and is almost equally conductive [26,27]. It has been reported that Ni/Cu-in comparison to Ag paste-has higher electrical conductivity and lower contact resistance, even at lower doping concentrations (N s ) [28].…”
Section: Silver Vs Copper Metallizationmentioning
confidence: 99%
“…There is an industrial push to replace the Ag front electrode 3,4]. The Ni layer is a barrier to block Cu diffusion into Si, which degrades the efficiency of the cell.…”
Section: Introductionmentioning
confidence: 99%